Nurses' Caring Behavior in Hospital: A Literature Review - Samsualam, Samsualam; Agus, Al Ihksan; Amir, Haeril (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The review was carried out using the PRISMA and PICO methods based on the search results of the BMC, IJCS, IJRPH, Science Direct and Wiley Online databases, with the keyword "Caring and Nursing Service" and the results obtained were 1216 articles. After screening the articles based in inclusion and exclusion criteria, for total 7 articles included in this review study. The patients were generally satisfied with the caring behavior of the nurses in the hospital, but the level of satisfaction of patients in private hospitals was higher than patients in public hospitals. Nurse caring behavior is the most important services for hospital, especially in government hospitals. Good nurse behavior has a positive effect on patient satisfaction and care in each hospital. Based on the research results, nurses have to apply caring behavior sufficiently to patients related to basic human needs